1989
DOI: 10.1002/polb.1989.090270103
|View full text |Cite
|
Sign up to set email alerts
|

Pressure dependence of the dielectric properties and phase transitions of polyvinylidene fluoride (PVDF) and a copolymer with trifluoroethylene

Abstract: The frequency, temperature, and hydrostatic pressure dependences of the dielectric properties, molecular relaxations, and phase transitions in PVDF and a copolymer with a 30 mol% trifluoroethylene were investigated. The β‐relaxation peak temperature Tβ and the melting temperature Tm of both polymers, and the ferroelectric transition temperature Tc of the copolymer, are strong increasing functions of pressure. The magnitudes of the pressure derivatives of Tβ, Tc, and Tm increase in the order of the “transition”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…The α c -relaxation is attributed to the rotation of the side groups dipoles or to the local oscillations of the frozen main chain [18]. The α a -relaxation near 260 K has been observed earlier in PVDF whereas the α c -relaxation appears as a kink near 380 K [19]. Similar results have been observed in the present investigations.…”
Section: Resultssupporting
confidence: 90%
“…The α c -relaxation is attributed to the rotation of the side groups dipoles or to the local oscillations of the frozen main chain [18]. The α a -relaxation near 260 K has been observed earlier in PVDF whereas the α c -relaxation appears as a kink near 380 K [19]. Similar results have been observed in the present investigations.…”
Section: Resultssupporting
confidence: 90%
“…Polymeric materials have a wide range of engineering applications [1,2], which stimulate huge interests in academics due to their fantastic mechanical, thermal and electrical properties [3e6]. The material properties of polymers are determined not only by their chemical composition but also by the mutual arrangement of their macromolecule [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer and polymer‐based composites have been investigated for a wide range of engineering applications including high strain rate condition, for example, shock‐wave loading . In particular, recent experimental and computational studies have demonstrated that polyurea, which falls into the class of elastomeric copolymers, have great potentials for the dispersion/attenuation of the shock waves resulting from the blast and/or ballistic impact loading .…”
Section: Introductionmentioning
confidence: 99%